2008
DOI: 10.1002/anie.200705880
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Theory Reveal the Fundamental Difference between Two‐State and Single‐State Reactivity Patterns in Nonheme FeIVO versus RuIVO Oxidants

Abstract: Two‐state reactivity involving close triplet ground and quintet excited states is responsible for the opposite reactivity trends of FeIV oxo complexes in O‐transfer and H‐abstraction reactions in dependence on the electron richness of the axial ligand X (see picture), as shown by comparison with RuIV analogues, in which both reactivities are solely governed by the electrophilicity of the complex because the quintet state is inaccessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…The TSR concepts showed that the involvement of the quintet state in the reaction is the root cause of these unusual reactivity patterns. Further validation of the TSR model was obtained from a more recent study on the corresponding [Ru IV (O)TMC(X)] z+ oxidants, where the quintet state is too high to be able to participate in the reaction;[11] this study revealed that the two reaction series exhibit precisely the same trends, indicative of the sole involvement of the triplet state.…”
mentioning
confidence: 89%
“…The TSR concepts showed that the involvement of the quintet state in the reaction is the root cause of these unusual reactivity patterns. Further validation of the TSR model was obtained from a more recent study on the corresponding [Ru IV (O)TMC(X)] z+ oxidants, where the quintet state is too high to be able to participate in the reaction;[11] this study revealed that the two reaction series exhibit precisely the same trends, indicative of the sole involvement of the triplet state.…”
mentioning
confidence: 89%
“…Theoretical studies of such biomimetic models may not only identify the key elements that determine their chemical reactivities, but may also provide insight into intermediates and reactivities of parent enzymes (Shaik et al, 2007a; de Visser et al, 2013). To date, DFT calculations have been applied extensively to various types of non-heme iron species (Scheme 1) (Bassan et al, 2002, 2005a,b; Roelfes et al, 2003; Decker and Solomon, 2005; Kumar et al, 2005; Quinonero et al, 2005; Berry et al, 2006; Bernasconi et al, 2007, 2011; de Visser, 2006, 2010; Hirao et al, 2006a, 2008a,b, 2011; Rohde et al, 2006; Decker et al, 2007; de Visser et al, 2007, 2011; Johansson et al, 2007; Noack and Siegbahn, 2007; Sastri et al, 2007; Sicking et al, 2007; Bernasconi and Baerends, 2008, 2013; Comba et al, 2008; Dhuri et al, 2008; Fiedler and Que, 2009; Klinker et al, 2009; Wang et al, 2009a, 2013b; Cho et al, 2010, 2012a, 2013; Geng et al, 2010; Chen et al, 2011; Chung et al, 2011b; Seo et al, 2011; Shaik et al, 2011; Vardhaman et al, 2011; Wong et al, 2011; Ye and Neese, 2011; Gonzalez-Ovalle et al, 2012; Gopakumar et al, 2012; Latifi et al, 2012; Mas-Ballesté et al, 2012; McDonald et al, 2012; Van Heuvelen et al, 2012; Ansari et al, 2013; Kim et al, 2013; Lee et al, 2013; Sahu et al, 2013; Tang et al, 2013; Ye et al, 2013; Hong et al, 2014; Sun et al, 2014). The intriguing reactivity patterns of these complexes are the result of active involvement of electrons in d-type MOs, which gives rise to multi-state scenarios (Shaik et al, 1998; Schröder et al, 2000; Schwarz, 2011).…”
Section: Applications Of Dftmentioning
confidence: 99%
“…This mode of binding mimics that of the obligate tetradentate tetramethylated cyclam (N-Me 4 cyclam). [20][21][22][23][24] Indeed, the structural, spectroscopic, and electrochemical properties of the Cu II and Ni Although demetalation of any hexadentate sar-type complex should proceed through such partially (e.g., tetradentate) coordinated forms of the ligand, identification of these intermediates is difficult given the harsh conditions required to remove the metal from the cage. Complete removal of Co from sar-derived cages can only be achieved after reduction to the less stable and more labile Co II form, followed by either complexation with cyanide or protonation of the free ligand.…”
Section: Introductionmentioning
confidence: 99%